Secondary prevention and cardiovascular care across Europe: A survey of European Society of Cardiology members' views. (March 2020) - Fitzsimons, Donna; Stępińska, Janina; Kerins, Mary; F Piepoli, Massimo; Hill, Loreena; Carson, Matthew A; Prescott, Eva
Introduction: Secondary prevention of cardiovascular disease is a significant clinical challenge and despite European Society of Cardiology (ESC) Guidelines, evidence confirms sub-optimal patient care. Aim: The aim of this study was to evaluate ESC members' opinions on the current provision of cardiovascular prevention and rehabilitation services across Europe and explore barriers to guideline implementation. Method: Electronic surveys using a secure web link were sent to members of the ESC in eight purposively selected ESC affiliated countries. Results: A total of 479 professionals completed the survey, of whom 67% were cardiologists, 8.6% general physicians, 8.2% nurses and 16.2% other healthcare professionals. Respondents were predominantly (91%) practising clinicians, generally highly motivated regarding cardiovascular disease prevention, but most reported that secondary prevention in their country was sub-optimal. The main barriers to prevention were lack of available cardiac rehabilitation programmes and long-term follow-up, patients' disease perception and professional attitudes towards prevention. While knowledge of the prevention guidelines was generally good, practices such as motivational counselling and better educational tools were called for to promote exercise, smoking cessation and for nutritional aspects. Conclusions: The provision of services focusing on the secondary prevention of cardiovascular disease varies greatly across Europe. Furthermore, despite ESC Guidelines and a strong evidence base supporting the efficacy of secondary prevention, the infrastructure and co-ordination of such care is lacking. In addition patient motivation is considered poor and some professionals remain unconvinced about the merits of prevention. The disappointing results outlined in this survey emphasise that improved tools are urgently required to educate both patients and professionals and confirm the priority of cardiovascular prevention internationally.